2018
DOI: 10.1142/s0217732318501031
|View full text |Cite
|
Sign up to set email alerts
|

Hidden messenger from quantum geometry: Towards information conservation in quantum gravity

Abstract: The back reactions of Hawking radiation allow nontrivial correlations between consecutive Hawking quanta, which gives a possible way of resolving the paradox of black hole information loss known as the hidden messenger method. In a recent work of Ma et al [arXiv:1711.10704], this method is enhanced by a general derivation using small deviations of the states of Hawking quanta off canonical typicality. In this paper, we use this typicality argument to study the effects of generic back reactions on the quantum g… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 29 publications
(64 reference statements)
0
4
0
Order By: Relevance
“…25 The link of quantum gravity and quantum information or entanglement is an idea not unexpected for contemporary physics: on the contrary, a series of papers (Kay 2018;Ma 2018;Qi 2018;Donnelly, Giddings 2017;Marletto, Vedral 2017;Ruiz, Giacomini, Brukner 2017;Lee, Kim, Lee 2015;Bruschi, Sabín, White, Baccetti, Oi, Fuentes 2014;Nomura, Varela, Weinberg 2013;Resconi, Licata, Fiscaletti 2013;Dvali, Gomez 2009;Fursaev 2008;Girelli, Livine 2005;Moffat 2004;Peres 2004) discusses it, including information conservation (e.g. Guo, Cai 2018) or information theory (Kempf 2018;Kempf, Martin 2008;Sato 2007;Carol 2005). Furthermore, the pathway to quantum gravity by the mediation of information or quantum information is often traced (as in the present paper) by more or less philosophical considerations or arguments (e.g.…”
Section: Why Entanglement Was Neglectedmentioning
confidence: 99%
“…25 The link of quantum gravity and quantum information or entanglement is an idea not unexpected for contemporary physics: on the contrary, a series of papers (Kay 2018;Ma 2018;Qi 2018;Donnelly, Giddings 2017;Marletto, Vedral 2017;Ruiz, Giacomini, Brukner 2017;Lee, Kim, Lee 2015;Bruschi, Sabín, White, Baccetti, Oi, Fuentes 2014;Nomura, Varela, Weinberg 2013;Resconi, Licata, Fiscaletti 2013;Dvali, Gomez 2009;Fursaev 2008;Girelli, Livine 2005;Moffat 2004;Peres 2004) discusses it, including information conservation (e.g. Guo, Cai 2018) or information theory (Kempf 2018;Kempf, Martin 2008;Sato 2007;Carol 2005). Furthermore, the pathway to quantum gravity by the mediation of information or quantum information is often traced (as in the present paper) by more or less philosophical considerations or arguments (e.g.…”
Section: Why Entanglement Was Neglectedmentioning
confidence: 99%
“…To take into account the quantum nature of the shell and the spacetime determined by it, we follow the reduced phase space quantization procedure introduced in section II B. For this reason, we promote the observable quantities V and M , defined in (18) and (15), to operators satisfying the Heissenberg algebra…”
Section: The Infalling Quantum Shell and Hawking Radiationmentioning
confidence: 99%
“…Two-dimensional models of black holes were introduced some twenty five years ago [18][19][20][21][22]. Even though they are simpler than the four-dimensional case, most of the previously mentioned problems are still present [10,11,16,[23][24][25][26], and a complete quantum analysis of a collapsing system is still lacking. In this paper we start the study of a collapsing quantum shell of matter in two dimensions.…”
Section: Introductionmentioning
confidence: 99%
“…[15] Recently, a simple method for obtain-ing the radiation spectrum of a black hole was proposed by Ma et al [16] based on canonical typicality. In this way, Guo and Cai [17] showed that entropy is conserved in a loop quantum black hole, and in Ref. [18], the correlation of the black hole radiation added by the dark energy was studied.…”
Section: Introductionmentioning
confidence: 99%